Fertilizer demand-supply gap and avenues for policy revisits in Nepal: Fertilizer deman supply gap in Nepal - Gautam, Shriniwas; Gaihre, Yam Kanta; Acharya, Ganga Dutta; Dongol, Prabin; Choudhary, Dyutiman (SAARC Journal of Agriculture, 2022)
Nepal's farmers report fertilizer shortages yearly, especially for rice, wheat, and maize production. A reliable and established approach to estimating the actual demand for fertilizers for different crops and cropping seasons is lacking. Therefore, it is difficult to project the types and quantity of fertilizer to import and allocate across various regions in the country. With the direct involvement of the Government of Nepal (GoN) in fertilizer import, price (subsidy), and distribution, together with the high affinity of farmers for the subsidy, there is no incentive for the private sector to import and distribute fertilizers. Thus, farmers’ access to fertilizers in the country depends primarily on the subsidy budget, quantity and types of fertilizers imported, and their distribution management. In this study, the fertilizer demands, both at the national and sub-national levels, were estimated through a survey of cooperatives that distribute subsidized fertilizers in the country. Our estimate suggests that the fertilizer supplied in 2018/19 was only 60% of the total effective demand in the country. With this estimate of the demand-supply gap and the price variability across provinces, short, medium, and long-term policy recommendations are made to improve the supply of chemical fertilizer in the country SAARC J. Agric., 20(2): 223-234 (2022)